ORIENTASI PERKEMBANGAN PENDIDIKAN ISLAM PASCA PROKLAMASI - Fahmi, Fauzi (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2021)
Abstract Historical records reveal that Islamic education in Indonesia has its own characteristics and plays a major role in advancing Islamic culture in Indonesia. This research uses the library research method (Library Research) which relies on bibliographical sources from books and articles in scientific journals related to the subject matter. The findings of this study include: 1) After the proclamation of Indonesian independence, there are four kinds of education for Muslims in Indonesia, including: madrasas, Islamic boarding schools, government schools and Islamic schools. 2) The development of changes in Islam in Indonesia as a revival and renewal and enlightenment. 3) The Islamic education system that existed at that time and has developed as an effort and form of implementation of Islamic law so as to get guarantees and opportunities to continue to exist and develop.